Pengaruh Media Pembelajaran Explee Berbasis Video Interaktif Sebagai Penguatan Pendidikan Karakter Siswa Sekolah Dasar - Gesang Bagus Prastyo; Ari Metalin Ika Puspita; Wahyu Nurmalasari (Al-Aulad: Journal of Islamic Primary Education, 2021)
This research is motivated by the low character of the students of SDN 4 Pule and the lack of use of learning media in the teaching and learning process so that it does not attract the attention of students in the learning process at SDN 4 Pule. The purpose of this study is to determine the effect of learning media explee interactive video-based as strengthening character education. This research process uses quantitative methods using a one group pretest posttest design. The population of fifth grade students at SDN 4 Pule is 40 students. The sampling technique used in this study is saturated sampling. The sample in this study were all fifth grade students at SDN 4 Pule. The instruments used by researchers in data collection are interviews and questionnaires. Data analysis in this study used Paired Sample T-Test with the help of SPSS 25.0 Software. The results of the different test showed that the significance value was 0.00 (< 0.05). So, there are differences before and after the use of learning media explee interactive video-based. Based on the description above, it can be concluded that media is explee interactive video-based effective as a strengthening of character education for SDN 4 Pule students.